2001
DOI: 10.1002/aic.690471206
|View full text |Cite
|
Sign up to set email alerts
|

Drag and stability of objects in a yield stress fluid

Abstract: The drag force exerted on objects in a yield stress fluid was measured when the ®elocities become infinitely slow. In these quasi-static conditions, yield stress effects are predominant. Particular care was paid to determining the yield stress and checking interface conditions when characterizing these fluids from a rheometric standpoint. Drag coefficients could then be determined for interesting objects of ®arious shapes. The important role of fluid-object interface effects was also highlighted. On the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 12 publications
3
107
0
2
Order By: Relevance
“…The results for sphere S18 at these velocities are shown in Figure 7, for upward movement through Carbopol gel, and it is clear that as long as the velocity is low enough to exclude inertial effects, the results obtained are the same. This is in agreement with previous studies of low velocity sphere motion in yield stress materials, which have shown that the steady-state drag force is dominated by the yield stress rather than sphere velocity (Chafe and de Bruyn 2005, Jossic and Magnin 2001, Zhu et al 2001) and direct yield stress measurement using different rotational rates of the vane (Nguyen and Boger 1983). Kashani, J.L.…”
Section: Preprint Version Of Accepted Article Please Cite Assupporting
confidence: 92%
“…The results for sphere S18 at these velocities are shown in Figure 7, for upward movement through Carbopol gel, and it is clear that as long as the velocity is low enough to exclude inertial effects, the results obtained are the same. This is in agreement with previous studies of low velocity sphere motion in yield stress materials, which have shown that the steady-state drag force is dominated by the yield stress rather than sphere velocity (Chafe and de Bruyn 2005, Jossic and Magnin 2001, Zhu et al 2001) and direct yield stress measurement using different rotational rates of the vane (Nguyen and Boger 1983). Kashani, J.L.…”
Section: Preprint Version Of Accepted Article Please Cite Assupporting
confidence: 92%
“…(51) are approximate values. The coefficient 1.8 should be replaced by a function of n which is not known yet [10,11], and the coefficient 8 also depends on surface properties at the leading edge as well as at the rear of the plate. Eq.…”
Section: Unyielded Displacement At the Wallmentioning
confidence: 99%
“…These studies were extended to non-spherical solid inclusions by Jossic and Magnin (2001). Atapattu et al (1990) investigated wall effect for spheres falling in a viscoplastic medium at low Reynolds number and found that the effects are negligible for sphere-to-tube diameter ratio below some critical value.…”
Section: Introductionmentioning
confidence: 98%